Visualization of organ motion during breathing from 4D datasets - Müller, Markus; Karamalis, Athanasios; Navab, Nassir (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2013)
The introduction of 3D + t medical datasets is posing new challenges to visualization. Volumetric and flow visualization are established fields offering a wide spectrum of techniques for visualizing 3D + t datasets. In this work we address the problem of visualizing the motion of organs during breathing. As opposed to flow visualization we are not directly interested in the underlying flow, but in the deformation caused by the flow. Therefore, visualization of breathing motion focuses on emphasizing the organ motion while preserving the anatomical context provided by the volumetric visualization. In this work we will discuss methods from flow and volume visualization, their applications, and introduce alternative visualization approaches for enhancing the perception of organ motion due to breathing. © 2013 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 4D Visualization; Breathing; Deformation; Flow Visualization; Volume Rendering